DbHDPLS: A database of human disease-related protein-ligand structures. (February 2019) - Zhu, Muchun; Song, Xiaoping; Chen, Peng; Wang, Wenyan; Wang, Bing
Abstract: Protein-ligand complexes perform specific functions, most of which are related to human diseases. The database, called as human disease-related protein-ligand structures (dbHDPLS), collected 8833 structures which were extracted from protein data bank (PDB) and other related databases. The database is annotated with comprehensive information involving ligands and drugs, related human diseases and protein-ligand interaction information, with the information of protein structures. The database may be a reliable resource for structure-based drug target discoveries and druggability predictions of protein-ligand binding sites, drug-disease relationships based on protein-ligand complex structures. It can be publicly accessed at the website:http://DeepLearner.ahu.edu.cn/web/dbDPLS/ .